Challenges in the design of coordination polymers of the zinc-triad 1,1-dithiolates - Tiekink, Edward R. T. * (2017)
The phenomenon of metal-organic frameworks (coordination polymers) has proved to be a major contributor to the renaissance of coordination chemistry. The mainstay of generating coordination polymers has been the combination of carboxylic acids and pyridyl donors, either of which can be mono-, bi, tri-functional, etc. giving rise to zero-, one-, two- and, ultimately, three-dimensional architectures. An underrepresented class of ligands in this context are those where the anions are drawn from the 1,1-dithiolate class of ligand, e.g. xanthate [-S2COR], dithiophosphate [- S2P(OR)ORꞌ] and dithiocarbamate [-S2CNRRꞌ]. In this contribution, several general themes in the solid-state chemistry of binary zinc-triad 1,1-dithiolates [M = Zn, Cd and Hg; R/Rꞌ = alkyl, aryl] and their adducts with bipyridyl donors will be covered, starting with an overview of the importance of steric effects associated with 1,1- dithiolate ligand-bounds R groups. A consideration of the coordination polymers formed by xanthates, dithiophosphates and then dithiocarbamates will be given, illustrating that not all 1,1-dithiolate ligands are quite the same. The focus will continue with dithiocarbamate ligands in that the influence of introducing hydrogenbonding functionality into the ligands will be discussed. In summary, there are still many interesting discoveries to be made in the structural chemistry of zinc-triad 1,1- dithiolates and their derivatives.